2022
DOI: 10.3390/jcm11092517
|View full text |Cite
|
Sign up to set email alerts
|

Is Poor Lithium Response in Individuals with Bipolar Disorder Associated with Increased Degradation of Tryptophan along the Kynurenine Pathway? Results of an Exploratory Study

Abstract: Bipolar disorder is associated with an inflammation-triggered elevated catabolism of tryptophan to the kynurenine pathway, which impacts psychiatric symptoms and outcomes. The data indicate that lithium exerts anti-inflammatory effects by inhibiting indoleamine-2,3-dioxygenase (IDO)-1 activity. This exploratory study aimed to investigate the tryptophan catabolism in individuals with bipolar disorder (n = 48) compared to healthy controls (n = 48), and the associations with the response to mood stabilizers such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 78 publications
(109 reference statements)
2
11
0
Order By: Relevance
“…Our study found that tryptophan metabolites did not seem to be closely related to mania symptoms and reduction ratio. It has also been shown previously that tryptophan metabolites have no effect on lamotrigine and valproate response, only high levels of TRP, KYN/TRP, QUIN were associated with poor response to lithium, but less than one fifth of our BD-D patients were taking lithium (7). Previous studies have also shown that tryptophan metabolic index (plasma tryptophan/amino acids) was related to YMRS reduction ratio (62).…”
Section: Relationship Between Tryptophan and Kynurenine Metabolite An...supporting
confidence: 71%
See 1 more Smart Citation
“…Our study found that tryptophan metabolites did not seem to be closely related to mania symptoms and reduction ratio. It has also been shown previously that tryptophan metabolites have no effect on lamotrigine and valproate response, only high levels of TRP, KYN/TRP, QUIN were associated with poor response to lithium, but less than one fifth of our BD-D patients were taking lithium (7). Previous studies have also shown that tryptophan metabolic index (plasma tryptophan/amino acids) was related to YMRS reduction ratio (62).…”
Section: Relationship Between Tryptophan and Kynurenine Metabolite An...supporting
confidence: 71%
“…This pathway regulates the level of tryptophan (6). Kynurenic acid (KYNA) and quinolinic acid (QUIN) as produced by the metabolism have neuroprotective and neurotoxic effects, respectively, and the balance between the two metabolites plays important role in glutamatergic neurotransmission (7,8). The remaining 5% of tryptophan is metabolized into 5hydroxytryptophan (5-HTP) under the action of tryptophan hydroxylase, and 5-HTP is further metabolized into serotonin or 5-HT; under the action of aromatic L-amino acid decarboxylase.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lithium, a highly pleiotropic agent, interacting with several different molecular targets, may counteract TRP catabolism by inhibiting the inflammation-induced TRP breakdown [38]. Consistently, a recent study estimated an association of poorer response to lithium with higher levels of KYN, the KYN/TRP ratio, and QA, which could indicate a pro-inflammatory state with a higher degradation of TRP towards the neurotoxic branch [39].…”
Section: Summary and Interpretation Of Findingsmentioning
confidence: 79%
“…The study sample has been the subject of previous reports [ 24 , 25 ] and comprises 50 individuals affected by BD and 48 healthy controls (HC) recruited consecutively from 2019 to 2021 at the Unit of Psychiatry of the University of Cagliari and University Hospital Agency. This study aims to test for the association between genetics, gut microbiota, TRP metabolism through KYN and 5-HT with BD illness trajectories.…”
Section: Methodsmentioning
confidence: 99%
“…The employed laboratory analyses have been described in previous reports [ 24 , 25 , 36 , 37 , 38 ]. Blood samples were gathered in the early morning for each of the recruited subjects with EDTA tubes, immediately centrifuged at 2500 rpm at 4 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%